Determination of Employee Retention: Skills, Rewards and Relationship between Employees (Literature Review) - Hermawan, Eric (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The Literature Review Article on Determination of Employee Retention: Skills, Rewards and Relationships between Employees is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Skills are related to Employee Retention; 2) Rewards related to Employee Retention; and 3) Relationships between Employees related to Employee Retention. Apart from these 3 exogenous variables that affect the endogenous variable Employee Retention, there are still many other factors including performance, behavior and motivation variables.